Experimental (X-ray Diffraction and FT-IR) and Quantum Chemical Studies (HF and DFT) of Ethyl 3-hydroxy-7-methyl3-(3-methyl-3-phenylcyclobutyl)-5-phenyl-3,5-dihydro-5Hthiazolo [3,2-a]pyrimidine-6-carboxylate - Şen, Fatih; Yılmaz, Ibrahim; Dinçer, Muharrem; Çukurovalı, Alaaddin (My University, 2017)
The title compound, ethyl 3-hydroxy-7-methyl-3-(3-methyl-3-phenylcyclobutyl)-5-phenyl-3,5-dihydro-5Hthiazolo[3,2-?]pyrimidine-6-carboxylate, was synthesized and characterized by experimental and quantum chemical methods. The crystal structure of compound was brought to light by single crystal X-ray diffraction method and its vibrational spectrum (FT-IR) in solid state was observed in the region 4000-400 cm-1. The molecular geometry was those obtained from the X-ray structure determination was optimized using HartreeFock and Density Functional Theory (DFT/B3LYP) method with the 6-31G(d) basis set in ground state. From the optimized geometry of the molecule, geometric parameters (bond lengths, bond angles, torsion angles) and vibrational assignments of the compound have been theoretically calculated and compared with the experimental data. The obtained structural and vibrational results are well in agreement with the experimental measurement. The frontier molecular orbital (FMO) and Mulliken population analysis of the optimized geometries were investigated by theoretical calculation results.
Keywords: Spektroskopi; Kimya; Uygulamalı; Kimya; Organik; Kimya; Tıbbi